Elucidation of operation and degradation mechanisms of efficient organic solar cells - 유신영 (The Graduate School, Ajou University, 2022)
In this paper, we fabricated an inverted type of organic solar cell based on a non-fullerene acceptor (Y6). We measured the light intensity dependent JV characteristics of the devices and analyzed them using a computational simulation method. JV characteristic curves measured at various illuminances were able to be reproduced through the computational simulation with appropriate parameters. Through this, we confirmed that the light intensity dependence of the performance parameters of organic solar cells is closely related to the light intensity dependence of the bimolecular recombination and the SRH recombination, which are components of the recombination current. And we also confirmed that the device's performance is closely related to the dominant competition between the recombination current components. On the other hand, the interpretation of the JV characteristic curve through computational simulation is too complicated. And the interpretation through the 'Shockley' equation, which can be substituted for the simulation, does not explain the light intensity dependence of the recombination current. We were able to derive simple approximate forms describing the light intensity dependence of the recombination current by solving the transport equation and the Poisson equation with simple assumptions. And using this, we found a way to confirm the dominant recombination mechanism from the light intensity dependence of JV characteristics. We investigated the performance degradation of organic solar cells over time through the abovementioned method and the simulation. As a result, we confirmed that the oxidation of the ZnO layer caused the performance degradation of the device. And we could know that the resistance of other parts of the device except for the active layer could affect the recombination current and thus the device's performance
학위논문(박사)--아주대학교 일반대학원 :에너지시스템학과,2022. 2
Keywords: light intensity dependence; operation mechanism; organic solar cells; simulation